Roles and Contribution Of Universities in Managing Controversial Issues in Community: Case Study Of UMP’s Involvement in Lynas Project - Badhrulhisham, Abdul Aziz (2013)
University's place as a paramount player in a global system increasingly driven by knowledge, information and ideas. Knowledge is replacing other resources as the main driver of economic growth and education has increasingly become the foundation for individual prosperity and social mobility.